(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
This article attempts to draw attention to the foundational role of the literary production of Juan Emar in the national letters, in particular, its fruitful dialogue with the antipoesía de Parra. It is proposed that both in Miltín 1934 and the Antipoesía de Parra we attend the practice of carnivalization of the divine-sublime. In this direction, both avant-garde poetics modulate one of the edges the “unfinished project of modernity” (Habermas): the simbolic death of God and the simbolic space; connotated by the topico of the spheres music. Topico that in both authors is given in a questioning of a critique of an aesthetic of the sublime; that prevailed in criticism of that period.